Pengetahuan Tentang Manajemen Laktasi pada Ibu Menyusui Mendukung Keberhasilan ASI Eksklusif - Rochmawati, Rochmawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The low coverage of exclusive breastfeeding in Indonesia (37.3%) far below the national target of 80% requires evidence-based interventions, one of which is through strengthening knowledge of lactation management. This study aims to analyze the relationship between the level of knowledge about lactation management and the success of exclusive breastfeeding among mothers with babies aged 6-12 months. Using a cross-sectional design with 85 respondents selected through purposive sampling in the working area of Ciseeng Public Health Center, Bogor Regency. Data collection used the Breastfeeding Knowledge Questionnaire (BFKQ) and Infant Feeding Practices Questionnaire (IFPQ) instruments. Results showed 58.8% of respondents had good knowledge and 70.6% successfully provided exclusive breastfeeding. Chi-square analysis confirmed a significant relationship between variables (p=0.003), with a 2.8 times higher probability of success in the well-informed group. The aspect of breastfeeding technique knowledge was identified as highest (72.9%), while handling lactation problems was lowest (41.2%). These findings emphasize the importance of structured education with emphasis on practical components of lactation management to increase exclusive breastfeeding coverage.